Protecting Nature: Religious Ecofeminism in Indigenous Women’s Movements - Adawiah, Rabiatul (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2023)
This study aims to analyse the indigenous women's movement to protect nature using the perspective of religious ecofeminism. The Indigenous People Alliance of Indonesia (Aliansi Masyarakat Adat Nusantara-AMAN) documented 13 cases of indigenous territory seizure, affecting 103,717 indigenous people and 251 hectares of indigenous territories. Consequently, the patterns of indigenous knowledge related to spirituality, as lived by indigenous women, prompt them to respond to the exploitation of nature. This research seeks to confirm the basic thesis of ecofeminism that links the domination of women and nature. The study employs qualitative methods, utilising text data from online media such as Twitter. The selection of data sources is based on the role of online media as a space for the representation of indigenous women and indigenous peoples. The main findings indicate that indigenous women have successfully positioned themselves at the forefront of nature protection through their movements. The indigenous women's movement to protect nature exemplifies a relationship based on indigenous understanding and knowledge, which is inseparable from the interpretation of nature itself. Equally important, the response of indigenous women reflects the interpretation of humans and nature as interdependent entities that provide sustenance, a concept known as religious ecofeminism. This concept embodies a cultural and religious understanding of the cosmology of life. The study contributes to raising awareness of the critical role of indigenous women in environmental conservation and demonstrates that their movements are grounded in religious ecofeminism values.